2019
DOI: 10.3390/s19245531
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a 10 nm Particle Number Portable Emissions Measurement System (PEMS)

Abstract: On-board portable emissions measurement systems (PEMS) are part of the type approval, in-service conformity, and market surveillance aspects of the European exhaust emissions regulation. Currently, only solid particles >23 nm are counted, but Europe will introduce a lower limit of 10 nm. In this study, we evaluated a 10-nm prototype portable system comparing it with laboratory systems measuring diesel, gasoline, and CNG (compressed natural gas) vehicles with emission levels ranging from approximately 2 × 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 58 publications
1
16
0
Order By: Relevance
“…Recently, it was also suggested that these sub-23 nm particles are nonvolatile in nature as their concentration did not change with different dilutions or using catalytic stripper [85]. Elastomer connectors, which was not the case at our tests, can release non-volatile particles at elevated temperatures [86]. Another possibility is that these particles consist of compounds with boiling points around 350 °C, which is the temperature of the evaporation tube of the PN system.…”
Section: Pn Instrumentationmentioning
confidence: 69%
“…Recently, it was also suggested that these sub-23 nm particles are nonvolatile in nature as their concentration did not change with different dilutions or using catalytic stripper [85]. Elastomer connectors, which was not the case at our tests, can release non-volatile particles at elevated temperatures [86]. Another possibility is that these particles consist of compounds with boiling points around 350 °C, which is the temperature of the evaporation tube of the PN system.…”
Section: Pn Instrumentationmentioning
confidence: 69%
“… PN-PEMS studies: Laboratory studies that compared PN-PEMS with PMP systems at the tailpipe or the dilution tunnel [ 30 , 31 , 32 , 33 ]. From the studies that investigated the 10 nm PEMS, only the 23 nm information was used [ 34 , 35 ]. Tailpipe studies: Laboratory studies that compared PMP systems at the tailpipe and the dilution tunnel [ 28 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…PN-PEMS studies: Laboratory studies that compared PN-PEMS with PMP systems at the tailpipe or the dilution tunnel [ 30 , 31 , 32 , 33 ]. From the studies that investigated the 10 nm PEMS, only the 23 nm information was used [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…The intention is to include the new methodology in the Global Technical Regulation (GTR) 15 for light-duty vehicles and in the near future apply it in the EU regulation. However, the research for PEMS fulfilling the future requirements is limited [39]. Most importantly, it is still not known how much the measurement uncertainty will be affected by the extension of the lower size from 23 nm to 10 nm.…”
Section: Introductionmentioning
confidence: 99%